Digital Transformation in Public Management Functions for Public Information Disclosure - Budi Gunawan; Barito Mulyo Ratmono; Paulus Israwan Setyoko (Universitas Sultan Ageng Tirtayasa, 2023)
This research emphasizes the conditioning of resources in the context of public management to create the openness of public information during digital transformation. A literature study from various databases related to managing resources in public management is analyzed. The intended resources include the latest technology used to protect data and privacy when discussing information disclosure in Indonesia. Digital transformation has led public management to improve and accelerate technological acceleration in the context of data analytics and create the openness of information for the public by government administrators. The strategy used to address this digital transformation in public management encompasses a comprehensive plan, including strong data protection policies, investment in technology infrastructure, and training for public employees. Thus, pieces of technology and performance management, open government, and human resource capacity development Public information disclosure results in transparency and accountability, information disclosure, and improving public services. Moreover, integrating technology into the public information ecosystem provides great potential for increasing openness, participation, and better public services.